2011
DOI: 10.1103/physrevb.84.060504
|View full text |Cite
|
Sign up to set email alerts
|

Topological phases and surface flat bands in superconductors without inversion symmetry

Abstract: We examine different topological phases in three-dimensional non-centrosymmetric superconductors with time-reversal symmetry by using three different types of topological invariants. Due to the bulk boundary correspondence, a non-zero value of any of these topological numbers indicates the appearance of zero-energy Andreev surface states. We find that some of these boundary modes in nodal superconducting phases are dispersionless, i.e., they form a topologically protected flat band. The region where the zero-e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
367
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 280 publications
(375 citation statements)
references
References 39 publications
7
367
1
Order By: Relevance
“…A zero voltage conductance peak can appear thus close to impurities, at a surface or close to crystal boundaries. 7,50,[53][54][55][56][57][58][59] An intriguing possibility is that some sort of unconventional superconductivity appears within the 2H -TaSe 2 sheets, either in the form of a d-wave order parameter or of sign changing superconductivity between different sheets. 47,60 Such a possibility would imply that the superconducting properties change from conventional s-wave in multilayers to unconventional reduced symmetry superconductivity when decreasing the thickness of the sample down to a single layer.…”
Section: Discussionmentioning
confidence: 99%
“…A zero voltage conductance peak can appear thus close to impurities, at a surface or close to crystal boundaries. 7,50,[53][54][55][56][57][58][59] An intriguing possibility is that some sort of unconventional superconductivity appears within the 2H -TaSe 2 sheets, either in the form of a d-wave order parameter or of sign changing superconductivity between different sheets. 47,60 Such a possibility would imply that the superconducting properties change from conventional s-wave in multilayers to unconventional reduced symmetry superconductivity when decreasing the thickness of the sample down to a single layer.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously connected with disorder effects 31 or with more exotic scenarios like Majorana fermions [32][33][34] and Andreev surface states 35 . It also appears for ballistic transport l e >> L, if there is some restricted area within N region [36][37][38] .…”
Section: Fig 4 (Color Online)mentioning
confidence: 99%
“…Recently, several authors have demonstrated that surface Andreev bound states with flat dispersion arise in certain topological superconductors, for example Cu x Bi 2 Se 3 [16] and noncentrosymmetric superconductors [17,18]. Their existence can be traced back to the nontrivial topology associated with the gapped bulk, and thus are topologically protected.…”
mentioning
confidence: 99%